Effectiveness of Project Based Learning Model Assisted by Ethnophysics of Traditional Games on Higher Order Thinking Skills of Grade XI Students - Tarigan, Kelimsa; Koto, Irwan; Medriati, Rosane; Risdianto, Eko; Defianti, Aprina (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2025)
The problems in this study can be seen in the varying motivation and interest of students in learning. This study aims to determine the effectiveness of PjBL model assisted by ethnophysics of traditional games on higher order thinking skills of grade XI students. This type of research is a quasi-experiment with nonequivalent control group design. The population of this study were students of class XI IPA with a total of 227 students with a sample of 76 students. Sampling used purposive sampling technique. The research data were analyzed with descriptive and inferential statistics with SPSS version 25 software. Based on the results of the inferential statistical test through the independent sample t-test test, it was found that the application of the PjBL model in physics learning aided by ethnophysics had an influence on higher order thinking skills (HOTS) at the Sig level. (????) = 0,05. The results of the Cohen's d effect size test (=0.753) state that the effect of physics learning with the PjBL model assisted by ethnophysics on HOTS of class XI students is in the medium category. The findings in this study, will make a very important contribution to physics learning. Teachers can integrate the PjBL model with the local culture approach, which will create more meaningful learning.